Butter cheese produced in Parintins - AM: processing and physicochemical characteristics - Souza, Terezinha Teixeira; Vieira, Rita Brito [UNESP]; Mendonca, Gean Augusto Pereira; Santos Junior, Jailton Ribeiro dos; Freitas, Denise Ribeiro (Inst Laticinios Candido Tostes, 2023)
Butter cheese is one of the most consumed and produced dairy products in Parintins city, State of Amazonas. This food product, in addition to contributing to rent of local milk producers, may in the future be recognized as a local intangible food heritage and contribute to the sustainable development of communities that hold this traditional knowledge. For this to happen, it is necessary that the way of making this food is known and documented. Therefore, this work was developed to carry out a diagnosis of the way of making, the processing conditions, and the physical -chemical composition of butter cheeses produced by producers in the municipality of Parintins. The difference observed in the physical -chemical composition of the cheeses is due to the diversity of knowledge and flavors of each producer who, based on historical and cultural characteristics, builds his traditional know-how. It is a food heritage that needs to be preserved, but important elements to produce safe food must be modified, such as the conditions of the milking place, processing, utensils, water quality, and packaging.
Keywords: amazon region; manteiga da terra; regional cheese